Paradigma Abu< Al-Fad}l Terhadap Hukum Fikih Ibadah dalam Tafsir Ayat Al-Ah{kam min Al-Qur’an Al-Karim - Shofa, Ida Kurnia (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2019)
A product of interpretation certainly has a special characteristic that is unique to a product of interpretation. From this uniqueness, a mufassir paradigm will emerge that is implied in his work. This research is oriented to answer the background of the writing of interpretation, and how the paradigm of Abu> al-Fad} l is in the interpretation of the verses of the fiqh law of worship. In general, a commentator writes his commentary based on his academic desires or demands. In contrast to mbah Fadhal, as her familiars are, writing her interpretive products begins with the teaching of Jalalain interpretation subjects in Madrasah Diniyyah Sunnatunnur Senori, Tuban, East Java, which she supports. According to Mbah Fadhal, his students will need a long time or even a lifetime to understand the whole meaning of the Qur'anic verses. Therefore, for time efficiency in learning interpretation, he collects and interprets verses that contain the laws of fiqh so that his students can easily understand the verses of the Koran used in practice in worship and daily social life. The method used by Abu> al-Fad} l is the method of maud} u'i ijma> li with the form tafsi> r bi al-ra'y and patterned fiqi> h Shafi'iyyah. Its interpretation products are presented in Arabic. The concept of reasoning carried out by Abu> al-Fad} l in its interpretation is by linguistic analysis, the rules of us} ul fiqh, and many refer to previous commentators. When viewed from the process of establishing a law (istinba> t} law), Abu> al-Fad} l is included in the category of moderate scholars, that is not too free in taking a law because it also refers to riwayah-riwayah (Hadi> th Prophet) and supported by the environmental conditions of Abu> al-Fad} l when he lived. The paradigm of Abu> al-Fad} l in its interpretation is that the Qur'an is the affirmation of God s acf} un li kulli zama> n wa then n that is practical, effective, and understandable.